ULTIMATE PROFIT MANAGEMENT maximizing profitability as you grow your business. - Skevofilax, Manny ([S.l.] : PRODUCTIVITY PRESS, 2024)
Use this book as a guide. In it, the author covers the most important aspects of reasonable, prudent growth that will avoid debt and allow you, your partners, and business associates a productive and non-stressful existence with a business that grows and profits correctly.
Don't Underprice Your Products/Services Because You Don't Have the Confidence to Ask for Your Value -- As You Make Sales to Similar Size Companies, Start Building Your Confidence and Then Dedicate a Portion of Your Sales and Marketing Efforts to Larger Companies -- Develop Ways to Increase the Value of Your Existing Products/Services to Your Customers -- Create New, Higher-Value Products and Services -- The Six Secrets to Successful Price Increases -- Notes -- Chapter 8: Using Technology to Reduce Costs and Boost Your Productivity -- Web Conferencing -- Accounting Software -- Email Software
Keywords: Profit -- Economic aspects; Profit -- Management; BUSINESS & ECONOMICS / Development / Business Development; BUSINESS & ECONOMICS / Strategic Planning; BUSINESS & ECONOMICS / Entrepreneurship